Development of agile-based website and field person application for construction project data management - Manullang, Jontinus; Sirait, Kamson; Purba, Sartika Dewi; Manik, Aditiarno; Lubis, Harmoko (Journal of Intelligent Decision Support System (IDSS), 2024)
This research discusses the creation of a website and Field Person application designed to assist the management of construction project data processing. This system allows company leaders to monitor projects in real-time and assist field heads in compiling work reports. The main functions implemented include material management, shopping data, equipment data, work progress data, incoming funds, material usage, material requests, wage requests, and wage payments. This research uses an object-oriented software development methodology with an Agile approach to ensure flexibility and responsiveness to changing user needs, and offers innovative solutions in construction project management by utilizing technology to improve efficiency and accuracy in project data management.